The Lost Greek Epitaph from Hārūnābād (aka Shāhābād, mod. Eslāmābād-e Gharb), Iran, and its Elusive Discoverer, ‘Mr. H.’ - Potts, Daniel T. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
There are many reasons to revisit old discoveries, particularly when they have sunk into relative oblivion. In the case of a Greek inscription from a town on the Great Khorasan Road, in the heart of Media, that has not been seen since 1844, no particular justification seems required of an attempt to extract as much meaning as possible from such a precious find and to properly recognise, for the first time, its discoverer.